Linking the Utilization of Clickbait Headlines and News Marketing Communication Strategy in Online Media - Rahma Santhi Zinaida; Siti Tanti Hardiyanti; Zaid Amin (Jurnal the Messenger, 2025)
Introduction: The competition in the news industry makes online media portal companies constantly bombard consumers with persuasive news, not a few online media use clickbait on news titles to attract readers to click the news. It turns that, click bait is also linking with the online media marketing communication strategy. The aimed of this research was to know the linking utilization of click bait headline as and marketing communication strategies in tribunsumsel.com.